Tunable copper oxide quantum dots: Electrochemical synthesis, characterization, and advanced applications - Sujinnapram, Supphadate; Kengtone, Kampeepan; Raktham, Chainarong; Hongsith, Kritsada; Choopun, Supab; Wongrerkdee, Sutthipoj (Communications in Science and Technology, 2025)
This work represents tunable copper oxide quantum dots (QDs) using an electrochemical synthesis in a mixture of electrolytes of citric acid (CA) and potassium chloride (KCl). The colloidal solutions showed a blue coloration, indicating quantum size effects and uniform dispersion of spherical QDs. The absorbance slightly decreased as the concentration of CA and KCl increased. PL studies indicated the maximum emission intensity at high CA and KCl concentrations due to great stabilization and surface-passivated quantum confinement effects. SAED confirmed polycrystalline structures of CuO and Cu2O depending on the concentration of CA and KCl. This possibility of tuning particle size and crystalline phases offers significant potential for advanced applications. For a demonstration of the QDs as an antibacterial agent, it demonstrates potential as an agent for inhibiting E. coli and S. aureus. Furthermore, the integration of the QDs with ZnO-based photocatalysts resulted in an enhanced photocatalytic degradation of methylene blue.